Timely or early? Breaking away from cobalt-reliant lithium-ion batteries - Ya You; Jun Lu (Next Materials, 2023)
The discovery and continual development of lithium-ion batteries (LIBs) are the keys to enabling the global implementation of smart devices and electric vehicles (EVs). On the cathode side, transitioning away from the highly priced cobalt has been a prerequisite for the grant mission of achieving complete vehicle electrification yet a major challenge for the battery research communities. In this perspective, from the aspects of material design and optimization, the current status and future contour of cathodes are sketched in pursuing the ever-increasing threshold of high-performance and low-cost LIBs.